SYSTEMS AND METHODS FOR MONITORING AND CONTROLLING A MANUFACTURING PROCESS USING CONTEXTUAL HYBRID DIGITAL TWIN - KRISHNA, ANKUR; BHOGINENI, SREEHARI KUMAR; BASAVARSU, PURUSHOTTHAM GAUTHAM (2024)
This disclosure relates generally to systems and methods for monitoring and controlling a manufacturing process using contextual hybrid digital twin. Data pertaining to the manufacturing process is obtained from a plurality of data generation sources which is further inputted to one or more physics based models and train machine learning models such that simulated data and real time tata is obtained. Further, a gap between the simulated data and the real time data is determined and learnt. The learnt gap is further minimized and an augmented set of models are obtained. The augmented set of models along with a set of soft-sensing data is used to create the contextual hybrid digital twin for the manufacturing process. The performance of the manufacturing process is monitored and controlled using a performance analytics and decision making enablers of the contextual hybrid digital twin respectively in real time.